2014
DOI: 10.3136/fstr.20.1005
|View full text |Cite
|
Sign up to set email alerts
|

The Vitro Fermentation of Six Functional Oligosaccharides by Clostridium butyricum TK2 and Clostridium butyricum CB8

Abstract: In vitro fermentation of six functional oligosaccharides including fructooligosaccharides (FOS), galactooligosaccharides (GOS), xylooligosaccharides (XOS), isomaltooligosaccharides (IMOS), raffinose andstachyose was performed by using Clostridium butyricum TK2 and Clostridium butyricum CB8. Among the six oligosaccharides, IMOS revealed the strongest fermentability for both strains, which was supported by the highest viable cells (10.1 ± 1.05 and 9.8 ± 0.41 log (CFU / mL)) and the highest levels of SCFA or buty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…The amount of butyrate produced by IM was 1.71 and 2.61 times higher than that of GO and XO, respectively. 54 In the study, MO treatment resulted in greater concentrations of acetate and butyrate in the ileum, which corresponded with our finding that MO improves the intestinal immune function. Furthermore, the addition of MO in the diet resulted in higher abundances of Firmicutes, Proteobacteria, and Streptococcus in the ileum and Proteobacteria and Firmicutes in the colon, but lowered the amount of Bacteroidota in the colon compared with the CON group.…”
Section: Discussionsupporting
confidence: 88%
“…The amount of butyrate produced by IM was 1.71 and 2.61 times higher than that of GO and XO, respectively. 54 In the study, MO treatment resulted in greater concentrations of acetate and butyrate in the ileum, which corresponded with our finding that MO improves the intestinal immune function. Furthermore, the addition of MO in the diet resulted in higher abundances of Firmicutes, Proteobacteria, and Streptococcus in the ileum and Proteobacteria and Firmicutes in the colon, but lowered the amount of Bacteroidota in the colon compared with the CON group.…”
Section: Discussionsupporting
confidence: 88%
“…Short-Chain Fatty Acid (SCFA) Analysis. The method for SCFA extraction was adapted from Wang et al 20 and modified. Briefly, 2 mL of the above supernatant was obtained and acidified with 0.4 mL of 50% (v/v) H 2 SO 4 and then extracted with 2 mL of absolute ether.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…An in vitro fermentation study compared the fermentability of six oligosaccharides using C. butyricum TK2 and C. butyricum CB8 strains. The results showed that isomalto-oligosaccharides had the strongest fermentability in both strains; however, SCFA production differed between the two strains ( Wang et al , 2014 ). Furthermore, the dietary probiotic C. butyricum could be found within the mucus layer, which was suggested to contribute to its action within the gut ( Xu et al , 2021a ; Mun et al , 2022 ).…”
Section: Butyricum Interacts With Gut Microbes Toregulate Intestinal ...mentioning
confidence: 97%